Operating Leverage and Stock Returns under Different Aggregate Funding Conditions - García-Feijóo, Luis; Jensen, Tyler K.; Koch, Paul D. (The Accounting Review, 2024)
ABSTRACT We document time-varying interrelations between aggregate funding conditions and the impact of operating leverage (OL) on stock returns. OL represents a primitive source of risk, which helps explain the well established unconditional relation between OL and future returns. However, the outperformance of firms with high OL occurs exclusively during periods of unconstrained funding. Although high OL represents operational inflexibility, when the Fed eases funding constraints, improved capital availability mitigates this inflexibility. Consequently, investors bid up the prices of stocks with high OL when aggregate funding constraints are loosened to reflect their lower risk and greater expected performance in unconstrained periods. Data Availability: Data are available from the public sources cited in the text. JEL Classifications: E22; E44; E52; G11; G12; G14.